Development of IgM-ELISA for diagnosis of recent infection of Japanese encephalitis virus in equines. (January 2022) - Sahu, Anamika; Dhanze, Himani; Singh, Vijayta; Mehta, Deepa; Gupta, Megha; Singh, Mithilesh; Vinod, V.K.; Gulati, B.R.
Abstract: Japanese encephalitis (JE) is a re-emerging mosquito borne disease, for which equines are most susceptible amongst all animals. Detection of specific immunoglobulin 'M' (IgM) is considered as an ideal way to diagnose recent JE virus infection in equines due to low virus load and short-term viremia. The present study was undertaken to develop a sensitive and specific recombinant NS1 protein based indirect IgM-ELISA and IgM capture (MAC) ELISA to diagnose recent infection of JEV in equines. Indirect IgM ELISA was standardized with relative diagnostic sensitivity and specificity of 100% and 88.5%, respectively. The validation of indirect IgM-ELISA in different laboratories revealed excellent reproducibility with Cohen's kappa value ranging between 0.84 and 1. The standardization of MAC ELISA was attempted using checker board titration method and non-specific binding of polyclonal anti-equine IgM capture antibody with anti-porcine IgG conjugate and with hyperimmune serum raised in swine against the antigen was observed. Hence, the MAC ELISA was standardized with monoclonal capture antibody; however, its diagnostic performance could not meet the satisfactory limit. Due to better sensitivity and less turnaround time, indirect IgM-ELISA was employed to screen 821 equine serum samples revealing 33.73% positivity of IgM antibodies against JEV in equine population of India. The high JEV sero-positivity warrants the need for vaccination in Indian equine population along with the demand for research focused towards anti-viral therapy. The indirect IgM-ELISA developed in the present study could be useful to diagnose acute or recent infection of JEV in equines as well as in sero-epidemiological studies.